(untitled) - Omura, George (San Francisco, CA, 2001)
Written by best-selling author George Omura, this fully revised edition leads users through common tasks, paves the way for intermediate skills, and delves into more advanced topics.
Keywords: Computer graphics,Đồ họa máy tính; Computer programs,Chương trình máy tính